Digital assets : pricing, allocation and regulation / edited by Reena Aggarwal [and three others]. - Aggarwal, Reena (Cambridge University Press, 2024)
The ecosystem of digital assets continues to change exponentially. In post-COVID times, digital assets may be seen as a cheaper, more liquid, and transparent safe haven compared to that offered by more traditional asset types. Inclusion of new digital assets, especially cryptocurrencies, in portfolios of standard financial assets has been the subject of some academic study, but the theoretical and practical implications of this new trend are not yet fully understood. Digital Assets is the first book to present a comprehensive review of studies on the valuation and pricing of cryptocurrencies and digital assets. Outlining a new research agenda aimed at understanding the fundamental drivers of the value of cryptocurrencies, it brings together an impressive line-up of academics and practitioners to provide a timely perspective on government responses and regulatory approaches towards digital assets, including the setting of new legal frameworks.